The effects of meditative music during imagery training on netball shooting performance - Hasbullah, Nor Haslinda (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Imagery is widely used psychological skill training for the enhancement of performance in sport as imagery can be used to exercise our mental to imagine something. Music is also used to enhance sport performance. The purpose of the present study was to look into the effect of using meditative music during imagery on netball performance. This is a pre-test — intervention - post test study design. Twenty-nine healthy undergraduate female students aged between 18 to 24 years old from Universiti Sains Malaysia participated in this study. Participants were novices in netball sport, were randomly divided into two-intervention conditions namely meditative music during imagery (MMI; n = 16) and no music during imagery (NMI, n = 13). The means scores and standard deviation of MMI is (Af = 19.063, SD = 0.042) and NMI is (M = 20.769, SD = 1.481). Before the pre-test, all participants were given a chance to try the netball shooting about three times in three different position to make them familiarise with the netball shooting. Netball performance was measured in three different positions with three different lengths, which were left position, middle position, and right position. Each position had three different lengths and all together, the participant had to shoot in nine different positions. During the intervention, all participants completed four weeks of imagery consisted of 12 sessions of imagery before conducting the post-test. SIAM was employed to check participants’ imagery ability. Participant’s anxiety and self - confidence were measured at week 1 and week 4 using the CSAI-2R and Self-Confidence prior to pre-test and post-test of performance. The result on SIAM showed that all participants have scored from moderate to high score in the subscales of imagery abilities. Thus, all participants were added to the study. Independent samples /-test showed that there was no significant difference between both group MMI and NMI for netball